Association of Obesity‐Related Hemodilution of Prostate‐Specific Antigen, Dihydrotestosterone, and Testosterone. Issue 5 (19th December 2016) - Klaassen, Zachary; Howard, Lauren E.; Moreira, Daniel M.; Andriole, Gerald L.; Terris, Martha K.; Freedland, Stephen J.
Abstract : BACKGROUND: Prostate‐specific antigen (PSA) hemodilution is the leading theory for lower PSA values in obese men. However, testosterone and dihydrotestosterone (DHT), which are necessary for PSA production, are reduced in obese men. We assessed the relationship of body mass index (BMI) and PSA, taking into consideration the effect of testosterone and DHT. METHODS: Among 8, 122 participants in Reduction by Dutasteride of Prostate Cancer Events (REDUCE), complete data were available for 7, 275. BMI was categorized as normal (<25 kg/m 2 ), overweight (25–29.9 kg/m 2 ), obese (30–34.9 kg/m 2 ), or moderate + severely obese (≥35 kg/m 2 ). Associations between BMI, testosterone, and DHT and the outcome variable of PSA were examined using linear regression. RESULTS: There were 1, 964 (27.0%) normal weight, 3, 826 (52.6%) overweight, 1, 200 (16.5%) obese, and 285 (3.9%) moderately + severely obese patients. With increasing BMI, there was a progressive decrease in PSA ( P = 0.02), increase in prostate volume ( P < 0.001), and decrease in both testosterone ( P < 0.001) and DHT ( P < 0.001). Using linear regression, increasing BMI was associated with decreasing serum PSA values. Furthermore, BMI remained inversely associated with PSA after individually adjusting for testosterone and DHT, as well as when adjusting for testosterone and DHT in the same model. Decreased androgen levels accounted for only 19% of the lower PSA in men with higher BMI. CONCLUSIONS: Only a fraction of lower PSA in obese men could be attributed to testosterone and DHT levels. The remaining factors explaining lower PSA are unaccounted for, presumably secondary to hemodilution associated with increased plasma volume in obese men. Prostate 77:466–470, 2017 . © 2016 Wiley Periodicals, Inc.